Long‐term follow‐up of RET Y791F carriers in Denmark 1994‐2017: A National Cohort Study. Issue 6 (15th January 2019) - Høxbroe Michaelsen, Sanne; Ornstrup, Marie Juul; Poulsen, Morten Møller; Bennedbæk, Finn Noe; Gaustadnes, Mette; Rossing, Maria; Darling, Peter; Vestergaard, Peter; Mathiesen, Jes Sloth
Abstract : Background and Objectives: Recently, a comprehensive study presented evidence that a long‐disputed REarranged during Transfection (RET) variant, RET Y791F, should be classified as nonpathogenic. In spite of this, several subsequently published papers, including the revised American Thyroid Association guidelines for medullary thyroid carcinoma, refer to the variant as pathogenic. This study presents data from a unique national Danish cohort of RET Y791F carriers who have been followed by watchful waiting instead of being subjected to early thyroidectomy, to determine if any carrier shows evidence of multiple endocrine neoplasia 2A (MEN2A) at long‐term follow‐up. Methods: A national cohort of all patients tested for RET mutations in Denmark from September 1994 to October 2017 was searched for carriers of RET Y791F. Medical records and laboratory reports of carriers were reviewed for signs of MEN2A at latest follow‐up (medullary thyroid carcinoma, primary hyperparathyroidism, pheochromocytoma, cutaneous lichen amyloidosis, or Hirschsprung's disease). Results: In total, twenty RET Y791F‐carriers were identified, none of whom showed any evidence of MEN2A, despite an age range from 7 to 87 years. Conclusions: Our national cohort study of all Danish RET Y791F carriers substantiates the claim that the RET Y791F variant is nonpathogenic.